2000
DOI: 10.1007/s00585-000-0653-2
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic control of the <i>fo</i>F2 long-term trends

Abstract: Abstract. Further development of the method proposed by Danilov and Mikhailov is presented. The method is applied to reveal the foF2 long-term trends on 30 Northern Hemisphere ionosonde stations. Most of them show signi®cant foF2 trends. A pronounced dependence of trend magnitude on geomagnetic (invariant) latitude is con®rmed. Periods of negative/positive foF2 trends corresponding to the periods of long-term increasing/ decreasing geomagnetic activity are revealed for the ®rst time. Pronounced diurnal variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…This is probably due to the fact that some other factors not considered could result in ionospheric variations. These factors include the long-term geomagnetic activity variations (Mikhailov & Marin, 2000), the long-term gravity wave variations (Hoffmann et al, 2011), and even volcanic eruptions (Zhang, 2017;Zhang & Holt, 2013). In addition, the NCAR-TIEGCM model was used in the simulation in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is probably due to the fact that some other factors not considered could result in ionospheric variations. These factors include the long-term geomagnetic activity variations (Mikhailov & Marin, 2000), the long-term gravity wave variations (Hoffmann et al, 2011), and even volcanic eruptions (Zhang, 2017;Zhang & Holt, 2013). In addition, the NCAR-TIEGCM model was used in the simulation in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Their study shows that the thermosphere will cool by about 10 K as the CO 2 mixing ratio is doubled. After that, huge efforts have been made on the long-term trend study in the ionosphere, thermosphere, and even mesosphere-lower-thermosphere (MLT) region through data analysis (Bremer, 2001;Danilov & Mikhailov, 2001;Emmert et al, 2012;Fang et al, 2012;Mikhailov & Marin, 2000;Ogawa et al, 2014;Yue et al, 2006;Zhang et al, 2016;Zhang & Holt, 2013) or theoretical simulation (Cnossen et al, 2011;Qian et al, 2011;Rishbeth & Roble, 1992;Solomon et al, 2015;Yue et al, 2008) or theoretical analysis (Akmaev, 2012;Elias, 2009). The community has achieved a common view regarding the long-term trend of a variety of physical parameters and their drivers in the upper atmosphere through comprehensive data analysis and simulations as summarized in several review papers (e.g., Laštovička et al, 2006Laštovička et al, , 2012Qian et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The next step was done by Mikhailov and Marin [2000] who have confirmed the dependence of f o F 2 trends on geomagnetic (invariant) latitude both for daytime and nighttime hours and have shown, for the first time, that there exist periods with negative and positive f o F 2 trends, which correspond to the periods of long-term increasing/decreasing geomagnetic activity. It was shown that trends (the sign) were strongly depended on the phase (rising/falling) of long-term varying geomagnetic activity, the 11 year running mean Ap index was considered as an indicator of these variations.…”
mentioning
confidence: 95%
“…In the case of the ionosphere, the long-term trends in electron density, and ion composition and temperature have been associated with three possible causes: increasing greenhouse gases (Robre and Dickinson [2], Hall and Cannon [3]), long-term variation in geomagnetic activity (Danilov and Mikhailov [4], Mikhailov and Marin [5]), and secular variation in Earth's magnetic field (Foppiano et al [6], Cnossen and Richmond [7]). Thus, long-term upper atmospheric observational data are necessary to understand the physical mechanism of the long-term variation in the upper atmosphere.…”
Section: Introductionmentioning
confidence: 99%